Attachment Security and Developmental Patterns of Growth in Executive Functioning During Early Elementary School. Issue 3 (29th May 2017) - Matte‐Gagné, Célia; Bernier, Annie; Sirois, Marie‐Soleil; Lalonde, Gabrielle; Hertz, Sarah
Abstract : Despite the extensive research demonstrating the importance of child executive functioning (EF) for school adjustment, little longitudinal work has formally examined developmental change in EF during the early school years. Based on a sample of 106 mother–child dyads, the current longitudinal study investigated patterns of growth in child performance on three executive tasks between kindergarten ( M age  = 6 years) and Grade 3 ( M age  = 9 years), and the predictive role of earlier mother–child attachment security in these patterns. The results suggest that early elementary school is a period of significant developmental improvement in child EF, although child performance on different EF tasks follows distinct trajectories across time. The study also provides evidence for a sustained relation between children's early attachment security and their ongoing acquisition of executive skills.